Yamada's handbook of gastroenterology - Yamada, Tadataka; Inadomi, John M. (Chichester, West Sussex : Wiley-Blackwell, 2013)
Portable, practical, and entirely clinical, this affordable guide to assessment and management of the entire range of gastroenterological complaints and conditions is ideally suited for use by GI fellows and specialists. The book is divided into two parts: symptom-focused and disease-focused. Features include key practice points, essentials of diagnosis, potential pitfalls, key web links, society guideline comparisons, case studies, and multiple choice questions. When you need answers in a hurry, turn to the most trusted name in gastroenterology: Yamada.
Includes index.
Revised edition of: Handbook of gastroenterology. 2nd ed. c2005.
Print version record.
Keywords: Gastroenterology -- Handbooks, manuals, etc; Gastrointestinal system -- Diseases -- Handbooks, manuals, etc; Gastrointestinal Diseases; MEDICAL -- Gastroenterology; Gastroenterology; Gastrointestinal system -- Diseases; Handbooks; Electronic books; Handbooks and manuals